1994
DOI: 10.1099/0022-1317-75-5-1053
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genotypes of Hepatitis C Virus by Sequence Comparisons in the Core, E1 and NS-5 Regions

Abstract: Isolates of hepatitis C virus (HCV) show considerable nucleotide sequence variability throughout the genome. Comparisons of complete genome sequences have been used as the basis of classification of HCV into a number of genotypes that show 67 to 77 % sequence similarity. In order to investigate whether sequence relationships between genotypes are equivalent in different regions of the genome, we have carried out formal sequence analysis of variants in the 5' non-coding region (5'NCR) and in the genes encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
180
1
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(190 citation statements)
references
References 28 publications
5
180
1
4
Order By: Relevance
“…Genetic variants of HCV are known to be widely spread around the world. Genotypes 1, 2 and 3 are found on all continents, but in some geographical areas, such as Africa and Southeast Asia, viral isolates are highly divergent and particular genotypes or subtypes are predominant (13)(14)(15)(16). These data suggest the existence of a long-term endemic infection in these areas and some investigators have hypothesized that HCV might have originated in such places (17).…”
Section: Discussionmentioning
confidence: 88%
“…Genetic variants of HCV are known to be widely spread around the world. Genotypes 1, 2 and 3 are found on all continents, but in some geographical areas, such as Africa and Southeast Asia, viral isolates are highly divergent and particular genotypes or subtypes are predominant (13)(14)(15)(16). These data suggest the existence of a long-term endemic infection in these areas and some investigators have hypothesized that HCV might have originated in such places (17).…”
Section: Discussionmentioning
confidence: 88%
“…First, this classification needs to be confirmed by studying other parts of the viral genome. Studies on HCV genetic heterogeneity have shown that nearly all HCV isolates segregated together in the same phylogenetic branch [14,15] for all genomic regions studied so far (5'-UTR, core, El, and NS5). To be scientifically certain, we believe that a similar approach, i.e., to confirm this phylogenetic relationship with other genomic regions, is important for definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Tolou et al, 2001;Uzcategui et al, 2001;, hepaciviruses (GB virus C/hepatitis G virus) (Worobey & Holmes, 2001) and Japanese encephalitis or St Louis encephalitis virus (Twiddy & Holmes, 2003). There have been few reports on recombination between HCV strains of different genotypes (Kalinina et al, 2002;Yun et al, 1996) and it has been suggested that these events are rare in vivo and that the resultant recombinants are usually not viable (Simmonds et al, 1994;Smith & Simmonds, 1997).…”
Section: Introductionmentioning
confidence: 99%